Long-term outcomes of metachronous neoplasms in the ileal pouch and rectum after surgical treatment in patients with familial adenomatous polyposis - Tajika, Masahiro; Tanaka, Tsutomu; Ishihara, Makoto; Hirayama, Yutaka; Oonishi, Sachiyo; Mizuno, Nobumasa; Kuwahara, Takamichi; Okuno, Nozomi; Matsumoto, Shinpei; Ooshiro, Taihei; Kinoshita, Takashi; Komori, Koji; Bhatia, Vikram; Hara, Kazuo; Yatabe, Yasushi; Niwa, Yasumasa (Endoscopy International Open, 2019)
Background and study aims Restorative proctocolectomy has become the most common surgical option for patients with familial adenomatous polyposis (FAP). However, adenomas and even carcinomas may develop in the ileal pouch over time. The aim of this study was to evaluate the long-term incidence and nature of ileal pouch or distal ileal adenomas and carcinomas in patients with FAP.Patients and methods This was a retrospective study of 47 FAP patients with Kock’s continent ileostomy (Kock) (n = 8), ileorectal anastomosis (IRA) (n = 13), and ileal pouch-anal anastomosis (IPAA) (n = 26). Patients were followed with a standardized protocol including chromoendoscopy and biopsies of visible polyps in the ileal pouch, distal ileum, and rectum every 6 to 12 months.Results Median follow-up was 21.0 years. Overall risk of adenoma development was significantly higher in IRA patients, with incidence rates of 85 % and 100 % at 5 and 10 years’ follow-up, respectively, compared to pouch patients (Kock + IPAA) (P < 0.001). However, there was also a high frequency of adenomas in the ileal pouch mucosa, with rates of 12 %, 33 %, and 68 %, at 5, 10, and 20 years of follow-up, respectively. Maximum size of ileal pouch adenomas was significantly related to time since surgery (P = 0.0214). Six cases of advanced adenomas including two cases of adenocarcinomas developed in the ileal pouch mucosa.Conclusions There is a significant incidence of adenoma(s) in the ileal pouch of FAP patients on long-term follow-up. Regular endoscopic surveillance is recommended, not only in IRA patients, but also in pouch patients after proctocolectomy.